A ilegitimidade democrática das decisões judiciais: a manutenção da supremacia judicial a partir da teoria dos diálogos institucionais no Brasil - Tiago Clemente Souza (2022)
One of the core issues that generates great concern and discomfort for legal theorists concerns not only the limits, but mainly the legitimacy of the decision-making processes that affect the collectivity. The tension between legality (stated legal system) and legitimacy takes place from the idea of democracy. The legal system that binds the behavior of citizens will only be legitimate when they are aware that, in some way, they contribute to the elaboration of legislation, to the process of attributing its meaning, to the inspection of its compliance and in the processes of reviewing the legislation. law. Thus, it is essential to verify the processes of legitimacy of decisions handed down by the Federal Supreme Court that face complex moral issues and that determine the recognition and limitation of citizens' rights. The present research seeks to investigate a third one regarding the tension between Judicial Supremacy and Legislative Supremacy in the process of construction of constitutional meaning, in which an overcoming of the last word conception is defended. It is in this context that the so-called Theories of Institutional Dialogues are presented with the intention of defending that it would not be up to any of the organs of Power to attribute the last final and definitive meaning of the constitutional text. In fact, all institutions, formal and non-formal, would enter into an always unfinished and dynamic enterprise of mutual cooperation and construction of constitutional meaning. On the other hand, it is necessary to investigate to what extent the Federal Supreme Court, by expressly appropriating the aforementioned dialogic perspective, effectively promotes dialogic relations with other non-legal institutions or, through mere strategic action, instrumentalizes theory to promote its supremacy in the process of construction of constitutional meaning. In addition, it is also necessary to verify to what extent it is possible to verify internal problems in the dialogic theories themselves that allow not only the overcoming of Judicial Supremacy, but also the maintenance and reinforcement of this dynamic.